Pelatihan Olahan Daging Kelinci Kelompok Desmigratif Tata Boga Desa Tegalretno, Petanahan, Kebumen, Jawa Tengah - Chalisty, Vian Dwi; Utami, Efrilia Tri Wahyu; Lutfiyani, Anisa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The Productive Migrant Village Program (desmigratif) is organized by the Ministry of Labour of the Republic of Indonesia to protect prospective Indonesian migrant workers (PMI) as well as retired PMI and their families. The desmigratif program is a concept for handling villages that are sending areas for migrant workers, which later, with cooperation from relevant ministries/institutions, can empower migrant workers and their families by utilizing local potential and the characteristics of the area. Based on kebumenupdate.com (2023), Kebumen as one of the districts in Central Java Province is ranked seventh as a district that contributes to the number of Indonesian migrant workers as many as 1,767 people, and at the national level, it is ranked 24th. One of the villages in Kebumen Regency which is a PMI pocket is Tegalretno Village, Petanahan District. Tegalretno Village, Petanahan District contributes as a contributor to the country's foreign exchange by sending migrant workers every year. The backgrounds that encourage people to work as migrant workers include low levels of education, few job opportunities, and the level of poverty in Indonesia. Several problems also arise in the process of becoming a PMI candidate or PMI whose contract has expired and returned to their area of origin. One of the problems highlighted after becoming a PMI is the lack of life skills and financial management so that the use of income while working as a PMI can be optimal. Tegalretno Village, Petanahan District, Kebumen Regency, Central Java Province is one of the villages designated by the Ministry of Manpower to empower PMI who have returned to their home villages. The empowerment activity for the retired PMI community chosen by the Tegalretno Village Office is through processing rabbit meat which is not widely sold on the market. This processed rabbit meat will later be sold in a rest area near Tegalretno Village so it is hoped that it can increase economic independence for retired PMIs and their families. Processed rabbit meat includes nuggets and meatballs.